Modified hard carbon material and preparation method thereof, negative plate and battery
By modifying the carbon source with polydiallyl dimethyl ammonium chloride (PDDA), the modified hard carbon material was prepared, which solved the problem of poor electrochemical performance of the negative electrode material of sodium ion battery and achieved efficient Cycle stability and rate performance improvements.
Patent Information
- Application Number
- CN202411025734.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
AI Technical Summary
The existing sodium ion battery anode materials have poor electrochemical performance due to the large radius and atomic mass of Na+, including low energy density, low cycle stability and low first-term efficiency, which is difficult to meet industrial needs, especially hard carbon materials. Defects are easily generated during the melting process, affecting its micromorphology and electrochemical properties.
Use polydiallyl dimethyl ammonium chloride (PDDA) as a modifier to modify the carbon source, prepare modified hard carbon materials through heat treatment, limit the formation and growth of graphitized domains, avoid defects, and expand Layer spacing improves conductivity and circulation capacity.
The electrochemical properties of hard carbon materials are significantly improved, including reversible specific capacity, first effect and cycle stability, and excellent rate performance and kinetic performance are obtained, which are suitable for sodium ion battery negative electrode materials.
Smart Images

Figure CN119133444A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a modified hard carbon material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] Although lithium-ion batteries have been widely used, the limited lithium resources and rising lithium prices have led to the need to find new alternative batteries. Although the capacity of sodium-ion batteries is not as good as that of lithium batteries, they are also a type of battery material that is expected to be industrialized. + ) The electrochemical performance of battery negative electrode materials cannot meet the actual industrial needs. + The larger radius and atomic mass result in poor sodium ion insertion and extraction kinetics, low energy density, poor cycle stability, and low initial efficiency. Therefore, conventional silicon-based negative electrode materials and graphite negative electrode materials are difficult to use in sodium ion batteries.
[0003] The most developed negative electrode materials for sodium ion batteries are hard carbon and soft carbon. Both are disordered carbon materials. The difference is that hard carbon has a low degree of graphitization, a richer disordered structure and a larger carbon layer spacing, which is convenient for Na + Embedding provides more active sites, and it is a sodium-ion battery negative electrode material that is expected to be industrialized. At present, hard carbon materials are a hot topic in sodium-ion battery research, especially biomass hard carbon materials. Due to their wide sources and low prices, they are low-cost, large-scale practical industrial production solutions for sodium-ion battery negative electrode materials. However, based on the performance of biomass hard carbon materials, their low capacity, low first efficiency, and low energy density make most of them in the research stage and have not yet been realized in large-scale practical applications. Among many materials, phenolic resin has a relatively simple and controllable molecular structure, and the relevant molecular structure can be designed according to needs, and the adjustable pore structure and active sites at the molecular level can be accurately constructed, so that hard carbon materials have better rate and cycle stability.
[0004] The electrochemical properties of hard carbon materials can be improved by doping modification, such as conductivity, first efficiency, capacity, etc. However, the existing heteroatom doping modification methods still have certain shortcomings. For example, the existing modifiers cannot avoid the generation of defects during the melting process, which is not conducive to the improvement of the microstructure of hard carbon materials and affects the electrochemical properties of the obtained hard carbon materials.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a modified hard carbon material and a preparation method thereof, a negative electrode sheet and a battery, which are conducive to improving the electrochemical performance of the hard carbon material.
[0007] In order to solve the above technical problems, this application is implemented as follows:
[0008] According to one aspect of the present application, an embodiment of the present application provides a modified hard carbon material, the modified hard carbon material comprising a carbon matrix and a doping element, the doping element being distributed between carbon layers of the carbon matrix, the doping element comprising an N element;
[0009] The modified hard carbon material is obtained by heat-treating a carbon source modified by a modifier, wherein the modifier comprises polydiallyldimethylammonium chloride.
[0010] In addition, the modified hard carbon material according to the present application may also have the following additional technical features:
[0011] In some embodiments, the carbon matrix has a carbon interlayer spacing of 0.3 nm to 0.5 nm.
[0012] In some embodiments, the mass of the N element accounts for 1% to 5% of the total mass of the modified hard carbon material.
[0013] In some of the embodiments, the modified hard carbon material has a fungus-like morphology.
[0014] In some embodiments, the carbon source includes an organic synthetic resin and / or a biomass resin, the organic synthetic resin includes at least one of a phenolic resin, an epoxy resin, a urea-formaldehyde resin, a melamine-formaldehyde resin, a polyester resin, a polyamide resin, an acrylic resin, a vinyl resin, a hydrocarbon resin or a polyether resin, and the biomass resin includes at least one of a starch phenolic resin, a lignin phenolic resin or a cellulose phenolic resin.
[0015] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a modified hard carbon material, the method comprising the following steps:
[0016] Mixing the carbon source solution and the modifier to obtain a mixture;
[0017] The mixture is mixed with a solvent, reacted at a first temperature for a first time, and dried to obtain a precursor;
[0018] heat-treating the precursor to obtain the modified hard carbon material;
[0019] Wherein, the modifier includes polydiallyldimethylammonium chloride.
[0020] In some embodiments, the carbon source solution includes a carbon source and an organic solvent; the carbon source includes an organic synthetic resin and / or a biomass resin, the organic synthetic resin includes at least one of a phenolic resin, an epoxy resin, a urea-formaldehyde resin, a melamine formaldehyde resin, a polyester resin, a polyamide resin, an acrylic resin, a vinyl resin, a hydrocarbon resin or a polyether resin, and the biomass resin includes at least one of a starch phenolic resin, a lignin phenolic resin or a cellulose phenolic resin.
[0021] In some embodiments, the organic solvent includes an alcohol solvent.
[0022] In some embodiments, the concentration of the carbon source solution is 1 to 10 mg / mL.
[0023] In some embodiments, the mass ratio of the modifier to the carbon source is 1:(5-10).
[0024] In some embodiments, the carbon source solution and the modifier are mixed at a mixing temperature of 40° C. to 100° C. and for a time of 2 h to 10 h.
[0025] In some embodiments, the solvent includes water, the carbon source solution includes a carbon source and an organic solvent, and the volume of the water is 1 to 5 times the volume of the organic solvent.
[0026] In some embodiments, the first temperature is 100° C. to 200° C., and the first time is 5 h to 10 h.
[0027] In some embodiments, the drying method is freeze-drying.
[0028] In some embodiments, the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially; the pre-oxidation treatment is a heat treatment at a second temperature for a second time; and the carbonization treatment is a heat treatment at a third temperature for a third time.
[0029] In some embodiments, the second temperature is 50° C. to 150° C., and the second time is 5 h to 20 h.
[0030] In some embodiments, the third temperature is 1000° C. to 1400° C., and the third time is 2 h to 5 h.
[0031] In some embodiments, the atmosphere during the pre-oxidation treatment includes air and / or oxygen.
[0032] In some embodiments, the atmosphere during the carbonization treatment includes at least one of nitrogen, argon, helium or neon.
[0033] In some embodiments, the heating rate of the pre-oxidation treatment is 0.5-5° C. / min.
[0034] In some embodiments, the heating rate of the carbonization treatment is 0.5-5°C / min.
[0035] According to another aspect of the present application, an embodiment of the present application provides a negative electrode plate, which includes the modified hard carbon material as described above or the modified hard carbon material prepared according to the above method.
[0036] According to another aspect of the present application, an embodiment of the present application provides a battery, which includes the aforementioned negative electrode sheet.
[0037] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0038] In the embodiment of the present application, the modified hard carbon material provided is obtained by heat treatment of a carbon source modified by a modifier, the modifier including polydiallyldimethylammonium chloride; and the carbon layers of the carbon matrix in the obtained modified hard carbon material are distributed with doping elements, the doping elements including N element, and the N element comes from the modifier. Therefore, the present invention creatively modifies the carbon source, introduces the modifier polydiallyldimethylammonium chloride (PDDA) into the carbon source to limit the formation and growth of graphitized domains, avoid the generation of defects during the melting process, improve the microscopic morphology, and is more conducive to improving the electrochemical properties of the hard carbon material. In particular, PDDA as a modifier can affect the pyrolysis process of the carbon source, limit the formation and growth of graphitized domains, effectively improve the thermal stability of the resin molecular chain, eliminate defects, enhance the structural disorder of the carbon material, and expand the interlayer spacing; at the same time, the amino group in PDDA as nitrogen (N) doping can improve the conductivity of the hard carbon material, thereby obtaining excellent rate performance; and by introducing N doping, the activity and electronic conductivity of the hard carbon material can also be improved, the specific surface area is increased, the defects are increased, and the ion adsorption capacity is improved, thereby improving the cycle capacity.
[0039] The modifier PDDA used in this application can simultaneously play the role of catalytic modification and doping modification, play a synergistic role, and can significantly improve the electrochemical properties of hard carbon materials, and its reversible specific capacity, first efficiency, and cycle stability are also improved.
[0040] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Shown is a SEM image of the modified hard carbon material prepared in Example 1 of the present invention.
[0042] Figure 2 Shown are the XRD patterns of the modified hard carbon material (PDDA@PF) prepared in Example 1 of the present invention and the common resin-based hard carbon material (PF).
[0043] Figure 3 Shown are the Raman spectra of the modified hard carbon material (PDDA@PF) prepared in Example 1 of the present invention and the common resin-based hard carbon material (PF). DETAILED DESCRIPTION
[0044] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0045] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0048] Hard carbon is considered to be a promising negative electrode material for sodium ion batteries due to its advantages such as large interlayer spacing, good structural stability and low cost. However, based on the performance of biomass hard carbon materials, its capacity is low and its initial efficiency is low. In other words, the existing resin-based hard carbon materials are limited in their further development in the field of negative electrodes for sodium ion batteries due to their poor reversible specific capacity and cycle performance. Therefore, it is necessary to modify the hard carbon materials to improve their electrochemical properties and enhance their application in the negative electrode of sodium ion batteries.
[0049] Modification of hard carbon materials by heteroatom doping has been proven to be an effective means to improve the electrochemical properties of hard carbon negative electrode materials. Among them, the introduction of N doping is a doping method that has been studied more. The introduction of N doping can improve the activity and electronic conductivity of hard carbon materials. In addition, N doping can increase the specific surface area, increase the number of defects, improve the ion adsorption capacity, and thus increase the ring capacity; nitrogen doping can also bring electrons to improve the conductivity of hard carbon, thereby obtaining excellent rate performance. However, the existing N doping still has certain shortcomings. For example, the modifier used cannot avoid the generation of defects during the melting process, which is not conducive to the improvement of the micromorphology of hard carbon materials, and other defects need to be further improved.
[0050] Therefore, it is necessary to fully consider the characteristics of hard carbon materials, improve the capacity and first efficiency of materials through modification, and avoid defects and influence on the morphology of materials during the modification process, so as to effectively alleviate the above problems. In view of this, the present application provides a modified hard carbon material and its preparation method, a negative electrode sheet and a battery, and the present application is described in detail below.
[0051] [Modified hard carbon materials]
[0052] In some embodiments, the present application provides a modified hard carbon material, which includes a carbon matrix and doping elements, wherein the doping elements are distributed between carbon layers of the carbon matrix, and the doping elements include N elements; the modified hard carbon material is obtained by heat treating a carbon source modified by a modifier, and the modifier includes polydiallyldimethylammonium chloride.
[0053] In the present application, the modified hard carbon material is obtained by heat treatment of a carbon source modified by a modifier, that is, the modified hard carbon material is a hard carbon material modified by a modifier, and it is particularly prominent that the modifier is selected from polydiallyldimethylammonium chloride (PDDA). Optionally, the carbon source can be a resin carbon source. Therefore, the inventors of the present application creatively modify the resin carbon source by PDDA, and improve the sodium storage performance of resin-derived carbon such as phenolic resin (PF) by adding PDDA to adjust the microstructure of the carbon.
[0054] In detail, the addition of PDDA will affect the pyrolysis process of resins such as phenolic resins, limit the formation and growth of graphitized domains, avoid the generation of defects during the melting process, improve the micromorphology, effectively improve the thermal stability of the resin molecular chain, eliminate defects to enhance the structural disorder of carbon materials, and expand the interlayer spacing, which is more conducive to improving the electrochemical properties of hard carbon materials. This is because PDDA uses its positive charge to affect the cross-linking process of resins such as phenolic resins; during the heat treatment process, resins such as phenolic resins initially reach a molten state, then gradually shrink and become brittle, and then serious foaming occurs; therefore, pyrolytic carbon of resins such as phenolic resins has the disadvantages of high structural regularity, narrow interlayer distance, strong porosity, and structural defects. The addition of PDDA can affect the pyrolysis process of phenolic resins, effectively limit the formation and growth of graphitized domains, avoid the generation of defects during the melting process, and improve the micromorphology. Therefore, the carbonization product has a high degree of lattice disorder and a large interlayer spacing, which is extremely beneficial to the storage of sodium ions. At the same time, PDDA contains amino groups, which can improve the conductivity of hard carbon as nitrogen (N) doping, thereby obtaining excellent rate performance.
[0055] In the present application, PDDA can simultaneously serve the purpose of catalytic modification and doping modification, exert a synergistic effect, and can significantly improve multiple electrochemical properties of hard carbon materials, and its reversible specific capacity, first efficiency, as well as cycle stability and rate performance can all be improved at the same time.
[0056] In the present application, the modified hard carbon material obtained by the above-mentioned PPDA modification includes a carbon matrix and a doping element, and the doping element is distributed between the carbon layers of the carbon matrix, and the doping element includes an N element. The introduction of the N element can improve the activity and electronic conductivity of the hard carbon material, increase the specific surface area, increase the number of defects, improve the ion adsorption capacity, and thus improve the cycle capacity. In addition, N doping can also bring electrons to improve the conductivity of the hard carbon, thereby obtaining excellent rate performance.
[0057] It should be understood that the present application mainly uses phenolic resin as an example to explain in detail the working principle of the modifier PDDA, but is not limited to this. That is, other types of resin carbon sources have the same or similar working principles, which will not be repeated here.
[0058] In some embodiments, the modified hard carbon material has a substantially fungus-like morphology, or a fungus-like shape.
[0059] Furthermore, the modified hard carbon material has a loose and porous wood ear-like morphology and structure, and this morphology and structure feature is conducive to improving the dynamic performance.
[0060] It should be pointed out that the "ear-shaped" mentioned in this article has a well-known meaning in the relevant field, such as various edible ear fungi commonly referred to. It can be understood in a conventional way and this application does not make any special limitation on this.
[0061] In the present application, the modified hard carbon material obtained by modifying the carbon source using PDDA can adjust the microstructure of the carbon, that is, improve the micromorphology, and obtain a modified hard carbon material with a fungus shape or similar to a fungus shape. Compared with the layered structure of conventional hard carbon, the hard carbon with a fungus-like morphology is easier to deintercalate and extract sodium ions, thereby improving the kinetic properties.
[0062] In some embodiments, the carbon interlayer spacing of the carbon matrix is 0.3nm to 0.5nm. Preferably, the carbon interlayer spacing of the carbon matrix is 0.37nm to 0.46nm. As an example, the carbon interlayer spacing of the carbon matrix can be any point value of 0.3nm, 0.32nm, 0.34nm, 0.35nm, 0.36nm, 0.37nm, 0.38nm, 0.4nm, 0.42nm, 0.45nm, 0.46nm, 0.48nm, 0.5nm or any range value between two thereof.
[0063] In the present application, the addition of PDDA can effectively improve the thermal stability of the resin molecular chain, eliminate defects, enhance the structural disorder of the carbon material, and expand the interlayer spacing; that is, while utilizing organic molecular intercalation to form a carbon layer, it also provides support between the layers and expands the interlayer spacing of the hard carbon material, thereby facilitating the improvement of the sodium ion storage performance.
[0064] In some embodiments, the mass of the N element accounts for 1% to 5% of the total mass of the modified hard carbon material. As an example, the mass of the N element accounts for any one of 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% of the total mass of the modified hard carbon material, or any range between two thereof.
[0065] By making the content of doped N element within the above-mentioned appropriate range, it helps to fully exert the basic properties of the hard carbon material, further improve the activity and electronic conductivity of the hard carbon material, improve the ion adsorption capacity, and also improve the cycle capacity, and also obtain excellent rate performance.
[0066] In some embodiments, the carbon source includes an organic synthetic resin and / or a biomass resin, that is, the carbon source may be an organic synthetic resin, a biomass resin, or a combination of an organic synthetic resin and a biomass resin.
[0067] Among them, the optional organic synthetic resin includes, but is not limited to, any one or a combination of at least two of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine formaldehyde resin, polyester resin, polyamide resin, acrylic resin, vinyl resin, hydrocarbon resin or polyether resin, and other resin derivatives. For the sake of brevity, the combinations within the above range are no longer listed one by one.
[0068] Optionally, the biomass resin includes, but is not limited to, any one or a combination of at least two of starch phenolic resin, lignin phenolic resin or cellulose phenolic resin, and other resin derivatives. For the sake of brevity, the combinations within the above range are not listed one by one.
[0069] Of course, it is not limited to this, and other similar synthetic resins or biological purification resins can also be used as long as they do not limit the purpose of this application.
[0070] In the present application, resins such as phenolic resins having R groups may be used, wherein the R groups are easily oxidized to become oxygen-containing functional groups, which can not only increase the interlayer spacing but also inhibit the formation of graphite domains and increase the degree of disorder.
[0071] In the present application, polydiallyldimethylammonium chloride (PDDA) is used as a modifier, which is positively charged after decomposition in water and is a quaternary amine linear chain organic substance with good conductivity. In addition, the PDDA modifier also has the following outstanding characteristics: (1) PDDA is a viscous liquid, which is loose and porous like fungus after carbonization; (2) PDDA is a polymer electrolyte with good conductivity, which can increase the conductivity of resin carbon materials; (3) PDDA contains N elements, which can meet the doping requirements while being modified, expand the interlayer spacing of the carbon layer, increase the sodium storage active sites, and inhibit the growth of graphite domains.
[0072] [Method for preparing modified hard carbon material]
[0073] In some embodiments, a method for preparing a modified hard carbon material is provided, the method comprising the following steps:
[0074] Mixing the carbon source solution and the modifier to obtain a mixture;
[0075] The mixture is mixed with a solvent, reacted at a first temperature for a first time, and dried to obtain a precursor;
[0076] heat-treating the precursor to obtain a modified hard carbon material;
[0077] Wherein, the modifier includes polydiallyldimethylammonium chloride.
[0078] In the present application, PDDA is introduced into a carbon source such as a resin carbon source for modification, and N element is in situ doped while catalyzing graphitization to prepare a resin-derived carbon material catalyzed by graphitization of organic matter, that is, a modified hard carbon material is obtained.
[0079] Thus, the sodium storage performance of the resin carbon source derived carbon is improved by adding PDDA to adjust the microstructure of the carbon. In addition, the addition of PDDA can effectively improve the thermal stability of the resin molecular chain, eliminate defects to enhance the structural disorder of the carbon material, and expand the interlayer spacing. At the same time, N doping brings electrons to improve the conductivity of hard carbon, thereby obtaining excellent rate performance. The PDDA in this application can simultaneously serve the purpose of catalytic modification and doping, play a synergistic role, and can significantly improve the reversible specific capacity, first effect, cycle stability and rate performance of hard carbon materials.
[0080] The embodiment of the present invention provides a method for preparing a modified hard carbon material. A carbon source solution and PDDA are mixed, reacted, and then heat treated to obtain a modified hard carbon material. The preparation method has a simple process, convenient operation, strong feasibility, and is easy to industrialize. By this method, a modified hard carbon material with a loose structure similar to that of wood ear can be prepared, which has good structural stability and good electrochemical properties.
[0081] It should be understood that all the features and advantages described above for the “modified hard carbon material” are also applicable to the “method for preparing the modified hard carbon material” and will not be described in detail here.
[0082] In some specific embodiments, the method for preparing the modified hard carbon material specifically comprises the following steps (a) to (c):
[0083] Step (a): mixing a carbon source solution and a modifier to obtain a mixture.
[0084] In some embodiments, in step (a), the carbon source solution is slowly added to the viscous modifier, and mixed and stirred at a certain temperature for a period of time to obtain a mixture, which is a pectin-like mixture.
[0085] Optionally, the mixing temperature of the carbon source solution and the modifier is 40°C to 100°C, and the time is 2h to 10h. Preferably, the mixing temperature of the carbon source solution and the modifier is 70°C to 90°C, and the time is 4h to 6h. As an example, the mixing and stirring temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, etc., and of course it can also be other values within the above range, which are not limited here; the mixing and stirring time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., and of course it can also be other values within the above range, which are not limited here.
[0086] Optionally, the mixed heating method is not limited to a water bath, and other methods such as an oil bath, a microwave method, etc. may also be applicable.
[0087] In some embodiments, in step (a), the carbon source solution includes a carbon source and an organic solvent, that is, the carbon source solution is prepared by dissolving the carbon source in an organic solvent. Optionally, the carbon source includes an organic synthetic resin and / or a biomass resin, the organic synthetic resin includes at least one of phenolic resin (PF), epoxy resin, urea-formaldehyde resin, melamine formaldehyde resin, polyester resin, polyamide resin, acrylic resin, vinyl resin, hydrocarbon resin or polyether resin, and the biomass resin includes at least one of starch phenolic resin, lignin phenolic resin or cellulose phenolic resin; in addition, the carbon source can also be other resin derivatives.
[0088] In the present application, resins such as phenolic resins having R groups may be used, wherein the R groups are easily oxidized to become oxygen-containing functional groups, which can not only increase the interlayer spacing but also inhibit the formation of graphite domains and increase the degree of disorder.
[0089] Optionally, the organic solvent includes an alcohol solvent. Optionally, the alcohol solvent can be a conventional alcohol solvent such as ethanol, methanol, propanol, etc., preferably ethanol. In this embodiment, the solvent used to dissolve the resin can be a conventional solvent, such as an alcohol solvent such as ethanol, but it is not limited thereto, as long as it can be used to dissolve the resin and is not limited to the purpose of this application.
[0090] In some embodiments, in step (a), the concentration of the carbon source solution is 1 to 10 mg / mL. For example, the carbon source solution can be an ethanol solution of a resin. As an example, the concentration of the carbon source solution can be 1 mg / mL, 2 mg / mL L, 4 mg / mL, 5 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, etc., and of course, it can also be other values within the above range, which are not limited here.
[0091] In some embodiments, in step (a), the mass ratio of the modifier to the carbon source is 1:(5-10), that is, the mass ratio of PDDA to the resin is 1:(5-10). As an example, the mass ratio of the modifier to the carbon source is 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., and of course it can be other values within the above range, which is not limited here.
[0092] Therefore, by controlling the mixing temperature, time, solution concentration, ratio of each substance and other conditions in step (a) within the above-mentioned range, it is helpful to fully mix the resin carbon source and the modifier, so that the content of the doping element is within an appropriate range, which helps to obtain a precursor material with excellent performance and can further improve the electrochemical performance of the modified hard carbon material product.
[0093] As an example, step (a) specifically includes: slowly adding the carbon source solution to the viscous modifier PDDA, mixing and stirring for 2h to 10h at a temperature of 40°C to 100°C (heating method can be a water bath, an oil bath, a microwave method, etc.), and obtaining a mixture, which is a pectin-like mixture. The carbon source solution can be an ethanol solution of the resin, the concentration of the carbon source solution is 1 to 10 mg / mL, and the mass ratio of the modifier to the carbon source is 1: (5 to 10).
[0094] Step (b): mixing the pectin-like mixture obtained in step (a) with a solvent, reacting at a first temperature for a first time, and drying to obtain a precursor.
[0095] Optionally, the solvent in step (b) may be water, such as deionized water.
[0096] In some embodiments, in step (b), the pectin-like mixture obtained in step (a) is added to a solvent such as deionized water, transferred into a polytetrafluoroethylene reactor, reacted at a first temperature for a first time, and dried to obtain a precursor; the precursor is a PDDA@resin (such as PF) precursor having a loose fungus shape.
[0097] In some embodiments, the volume of the solvent deionized water added in step (b) is 1 to 5 times the volume of the organic solvent such as ethanol in the carbon source solution in step (a). As an example, the volume of deionized water can be 1, 2, 3, 4, 5 times the volume of the alcohol solvent such as ethanol, etc., and of course it can also be other values within the above range, which is not limited here.
[0098] In some embodiments, in step (b), the first temperature is 100°C to 200°C, and the first time is 5h to 10h. As an example, the first temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., and of course it can also be other values within the above range, which is not limited here; the first time can be 5h, 6h, 7h, 8h, 9h, 10h, etc., and of course it can also be other values within the above range, which is not limited here.
[0099] Optionally, the heating method in step (b) is not limited to a water bath, and other methods such as an oil bath, a microwave method, etc. may also be applicable.
[0100] In some embodiments, in step (b), the drying method is freeze drying. By adopting the freeze drying method, the loose morphology of the PDDA@resin (such as PF) precursor material can be better maintained. The specific operating conditions of freeze drying can be selected and regulated by those skilled in the art according to actual conditions, and this application does not limit this.
[0101] Therefore, by controlling the reaction temperature, time and other conditions in step (b) within the above range, it helps to improve the microscopic morphology, help to obtain a loose fungus-like PDDA@resin precursor with excellent performance, and further improve the electrochemical performance of the modified hard carbon material product.
[0102] As an example, step (b) specifically includes: adding a solvent such as deionized water to the pectin-like mixture obtained in step (a), wherein the volume of the deionized water added is 1 to 5 times the volume of the organic solvent such as ethanol in the carbon source solution in step (a), transferring it into a polytetrafluoroethylene reactor, reacting it at 100° C. to 200° C. for 5 h to 10 h, and freeze-drying it to obtain a precursor; the precursor is a PDDA@resin (such as PF) precursor having a loose fungus shape.
[0103] Step (c): heat-treating the precursor obtained in step (b) to obtain a modified hard carbon material, that is, a loose wood ear-shaped in-situ N-doped organic matter-catalyzed graphitized resin-derived carbon material.
[0104] In some embodiments, in step (c), the heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially; the pre-oxidation treatment is a heat treatment at a second temperature for a second time; and the carbonization treatment is a heat treatment at a third temperature for a third time.
[0105] In the present application, the heat treatment is carried out in two steps, including a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment. The low-temperature pre-oxidation treatment can introduce oxygen-containing functional groups; the oxygen-containing functional groups escape during the subsequent high-temperature carbonization process, which is conducive to the expansion of the interlayer spacing.
[0106] Optionally, the heat treatment can be carried out in a tubular sintering furnace, and the heat treatment can be carried out in two steps, wherein the first step is a low-temperature pre-oxidation treatment, and the second step is a high-temperature carbonization treatment. The low-temperature pre-oxidation treatment is to heat the material to a second temperature at a first heating rate in a first atmosphere and then keep the temperature at the second temperature for a second time; the high-temperature carbonization treatment is to heat the material to a third temperature at a second heating rate in a second atmosphere and then keep the temperature at the third temperature for a third time.
[0107] In some embodiments, in the low-temperature pre-oxidation treatment, the second temperature is 50°C to 150°C, and the second time is 5h to 20h. As an example, the second temperature can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc., and of course it can also be other values within the above range, which is not limited here; the second time can be 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 15h, 18h, 20h, etc., and of course it can also be other values within the above range, which is not limited here.
[0108] In some embodiments, in the high temperature carbonization treatment, the third temperature is 1000°C to 1400°C, and the third time is 2h to 5h. As an example, the third temperature can be 1000°C, 1050°C, 1100°C, 1200°C, 1300°C, 1350°C, 1400°C, etc., and of course it can also be other values within the above range, which is not limited here; the third time can be 2h, 3h, 4h, 5h, etc., and of course it can also be other values within the above range, which is not limited here
[0109] In some embodiments, the atmosphere during the pre-oxidation treatment, ie, the first atmosphere, may include air and / or oxygen.
[0110] In some embodiments, the atmosphere during carbonization treatment, i.e., the second atmosphere, includes at least one of nitrogen, argon, helium or neon, preferably one or more of nitrogen, helium or argon. Optionally, the gas flow rate of the second atmosphere can be 40 to 80 mL / min, for example, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, etc.
[0111] In some embodiments, the heating rate of the pre-oxidation treatment, that is, the first heating rate, is 0.5 to 5°C / min. As an example, the first heating rate can be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., and of course, it can also be other values within the above range, which is not limited here.
[0112] In some embodiments, the heating rate of the carbonization treatment, that is, the second heating rate, is 0.5 to 5°C / min. As an example, the second heating rate can be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., and of course, it can also be other values within the above range, which is not limited here.
[0113] By controlling the temperature, time, heating rate and other conditions of the pre-oxidation and carbonization treatments of the modified hard carbon materials during the preparation process, it is helpful to obtain loose wood ear-like in-situ N-doped organic catalytic graphitized resin-derived carbon materials with excellent performance, which can further improve the electrochemical properties of the modified hard carbon material products.
[0114] As an example, step (c) of heat treating the precursor specifically includes: subjecting the precursor prepared in step (b) to a two-step heat treatment in a sintering furnace, the two-step heat treatment including: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein, the low-temperature pre-oxidation treatment includes: in an air or oxygen atmosphere, heating the temperature to 50°C to 150°C at a heating rate of 0.5 to 5°C / min and maintaining the temperature for 5h to 20h; the high-temperature carbonization treatment includes: in an atmosphere of at least one of nitrogen, helium, argon or neon, heating the temperature to 1000°C to 1400°C at a heating rate of 0.5 to 5°C / min and maintaining the temperature for 2h to 5h, wherein the gas flow rate can be 40 to 80mL / min; thereby, a modified hard carbon material can be obtained.
[0115] [Negative electrode]
[0116] In some embodiments, a negative electrode sheet is provided, which includes the modified hard carbon material as described above or the modified hard carbon material prepared according to the aforementioned method.
[0117] Since the negative electrode sheet includes the modified hard carbon material provided in the embodiments of the present application, it can exhibit good electrochemical properties, such as a higher first charge and discharge capacity, excellent first coulombic efficiency and good cycle stability.
[0118] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on two opposite surfaces of the negative electrode current collector. It is understood that the negative electrode active material layer can also be stacked on any one of the two surfaces of the negative electrode current collector.
[0119] The present application has no particular restrictions on the material of the negative electrode current collector, as long as the purpose of the present application can be achieved, it can be selected according to actual needs. As an example, the negative electrode current collector can be made of metal materials such as aluminum, copper, nickel, stainless steel, nickel-plated steel, or a foil with a surface coating layer made of a related foil material, which has one or more functionalities such as improving the conductivity, improving the adhesion, improving safety, reducing DCR, and increasing the lithium ion conduction ability, for example, it can be a carbon coating layer, carbon coating + graphene / conductive carbon tube / boehmite or alumina and solid electrolyte coating. Of course, in other embodiments, a composite current collector can also be used, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, etc.
[0120] In some embodiments, the negative electrode active material layer includes the modified hard carbon material provided in the present application as described above. Further, the negative electrode active material layer may also optionally include a conductive agent. Further, the negative electrode active material layer may also optionally include a binder.
[0121] The present application embodiment has no particular restrictions on the types of conductive agents and binders in the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber), polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose or sodium hydroxymethyl cellulose. The conductive agent may include but is not limited to at least one of conductive carbon black (Super P), conductive graphite, carbon nanotubes (CNTs), carbon fiber, graphene or conductive polymers. The above-mentioned conductive carbon black includes Ketjen black, acetylene black, etc., and the above-mentioned carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0122] The present application has no particular restriction on the mass ratio of the modified hard carbon material, the conductive agent, and the binder in the negative electrode active material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.
[0123] [Battery]
[0124] In some embodiments, a battery is provided, comprising the aforementioned negative electrode sheet.
[0125] Since the battery includes the modified hard carbon material provided in the embodiments of the present application, it can exhibit good electrochemical properties, such as a higher first charge and discharge capacity, excellent first coulombic efficiency and good cycle stability.
[0126] In the present application, the battery may be a sodium ion battery. The battery stacking type may be, for example, a winding type or a laminated type battery, and the structural type may be, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft pack battery, or a cylindrical battery, etc., without specific limitation. The battery has a high capacity, good cycle effect, and long service life.
[0127] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. That is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.
[0128] In the embodiments of the present application, in the battery, there is no limitation on the specific materials and structures of the positive electrode sheet, the separator, and the electrolyte, and any components and structures known in the art that can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.
[0129] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0130] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0131] Example 1
[0132] The preparation of the modified hard carbon material comprises the following steps:
[0133] (a) Slowly add 50 mg of viscous modifier PDDA to 50 mL of 5 mg / mL carbon source solution (PF ethanol solution) and disperse evenly, keep the mixture in a water bath at 80° C. and stir for 5 h to obtain a pectin-like mixture.
[0134] (b) The pectin-like mixture obtained in step (a) was added with 100 mL of deionized water, transferred into a polytetrafluoroethylene reactor, reacted at 120° C. for 8 h, and freeze-dried to obtain a PDDA@PF precursor having a loose fungus shape.
[0135] (c) subjecting the precursor obtained in step (b) to a two-step heat treatment, the two-step heat treatment comprising: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein the low-temperature pre-oxidation treatment comprises: in an air atmosphere, heating the temperature to 100°C at a heating rate of 2°C / min and maintaining the temperature for 8 hours; the high-temperature carbonization treatment comprises: in a nitrogen atmosphere, heating the temperature to 1200°C at a heating rate of 2°C / min and maintaining the temperature for 2 hours, to obtain a modified hard carbon material.
[0136] Example 2
[0137] The modified hard carbon material of Example 2 was prepared according to the preparation method of Example 1, except that:
[0138] In step (a), 50 mL of 5 mg / mL carbon source solution (PF ethanol solution) was slowly added with 25 mg of viscous modifier PDDA to disperse evenly, and the mixture was kept constant at 80° C. in a water bath and stirred for 5 h to obtain a pectin-like mixture.
[0139] Example 3
[0140] The modified hard carbon material of Example 3 was prepared according to the preparation method of Example 1, except that:
[0141] In step (a), 10 mg of viscous modifier PDDA was slowly added to 15 mL of 5 mg / mL carbon source solution (PF ethanol solution) and dispersed evenly, and the mixture was kept constant temperature at 80° C. in a water bath and stirred for 5 h to obtain a pectin-like mixture.
[0142] Example 4
[0143] The modified hard carbon material of Example 4 was prepared according to the preparation method of Example 1, except that:
[0144] The carbon source solution was adjusted to a melamine resin ethanol solution.
[0145] Example 5
[0146] The modified hard carbon material of Example 5 was prepared according to the preparation method of Example 1, except that:
[0147] In step (b), the pectin-like mixture obtained in step (a) is added with 100 mL of deionized water, transferred into a polytetrafluoroethylene reactor, reacted at 200° C. for 5 h, and freeze-dried to obtain a PDDA@PF precursor having a loose fungus shape.
[0148] Example 6
[0149] The modified hard carbon material of Example 6 was prepared according to the preparation method of Example 1, except that:
[0150] In step (c), the precursor prepared in step (b) is subjected to a two-step heat treatment, and the two-step heat treatment includes: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein the low-temperature pre-oxidation treatment includes: in an air atmosphere, heating the temperature to 120°C at a heating rate of 2°C / min and maintaining the temperature for 15 hours; the high-temperature carbonization treatment includes: in a nitrogen atmosphere, heating the temperature to 1200°C at a heating rate of 2°C / min and maintaining the temperature for 2 hours to obtain a modified hard carbon material.
[0151] Example 7
[0152] The modified hard carbon material of Example 7 was prepared according to the preparation method of Example 1, except that:
[0153] In step (c), the precursor prepared in step (b) is subjected to a two-step heat treatment, and the two-step heat treatment includes: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein the low-temperature pre-oxidation treatment includes: in an air atmosphere, heating the temperature to 120°C at a heating rate of 5°C / min and maintaining the temperature for 15 hours; the high-temperature carbonization treatment includes: in a nitrogen atmosphere, heating the temperature to 1200°C at a heating rate of 5°C / min and maintaining the temperature for 2 hours to obtain a modified hard carbon material.
[0154] Example 8
[0155] The modified hard carbon material of Example 8 was prepared according to the preparation method of Example 1, except that:
[0156] In step (c), the precursor prepared in step (b) is subjected to a two-step heat treatment, and the two-step heat treatment includes: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein the low-temperature pre-oxidation treatment includes: in an air atmosphere, heating the temperature to 120°C at a heating rate of 2°C / min and maintaining the temperature for 15 hours; the high-temperature carbonization treatment includes: in a nitrogen atmosphere, heating the temperature to 1000°C at a heating rate of 2°C / min and maintaining the temperature for 5 hours to obtain a modified hard carbon material.
[0157] Comparative Example 1
[0158] The preparation of the modified hard carbon material comprises the following steps:
[0159] (a) Slowly add 50 mL of 5 mg / mL carbon source solution (PF ethanol solution) to 50 mg of viscous modifier PDDA and disperse evenly, transfer to a polytetrafluoroethylene reactor, react at 120°C for 8 h, and obtain a precursor after freeze-drying.
[0160] (b) subjecting the precursor obtained in step (a) to a two-step heat treatment, the two-step heat treatment comprising: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein the low-temperature pre-oxidation treatment comprises: in an air atmosphere, heating the temperature to 100°C at a heating rate of 2°C / min and maintaining the temperature for 8 hours; the high-temperature carbonization treatment comprises: in a nitrogen atmosphere, heating the temperature to 1200°C at a heating rate of 2°C / min and maintaining the temperature for 2 hours, to obtain a modified hard carbon material.
[0161] The main difference between Comparative Example 1 and Example 1 is that Comparative Example 1 omits the step of heating in a water bath to cause ethanol to volatilize, which results in a denser structure of the organic matter-catalyzed graphitized resin carbon material obtained in Comparative Example 1.
[0162] Comparative Example 2
[0163] The preparation of the modified hard carbon material comprises the following steps:
[0164] (a) Slowly add 50 mL of 5 mg / mL carbon source solution (PF ethanol solution) to 50 mg of viscous modifier PDDA to disperse evenly, keep the mixture in a water bath at 80° C. and stir for 5 h to obtain a mixture.
[0165] (b) directly subjecting the mixture obtained in step (a) to heat treatment, including: low-temperature pre-oxidation treatment and high-temperature carbonization treatment; wherein, the low-temperature pre-oxidation treatment comprises: in an air atmosphere, heating the temperature to 100°C at a heating rate of 2°C / min and maintaining the temperature for 8 hours; the high-temperature carbonization treatment comprises: in a nitrogen atmosphere, heating the temperature to 1200°C at a heating rate of 2°C / min and maintaining the temperature for 2 hours, to obtain a modified hard carbon material.
[0166] The main difference between Comparative Example 2 and Example 1 is that Comparative Example 2 omits the previous step (b), that is, Comparative Example 2 does not undergo a hydrothermal process, cannot perform morphology processing and in-situ N doping, and is only a liquid phase mixing in a physical sense.
[0167] Comparative Example 3
[0168] The preparation of the modified hard carbon material comprises the following steps:
[0169] (a) 50 mg of melamine was slowly added to 50 mL of 5 mg / mL carbon source solution (PF ethanol solution) and stirred evenly, and then transferred into a polytetrafluoroethylene reactor and reacted at 120° C. for 8 h. After freeze-drying, an N-PF precursor was obtained.
[0170] (b) subjecting the N-PF precursor obtained in step (a) to a two-step heat treatment, the two-step heat treatment comprising: a low-temperature pre-oxidation treatment and a high-temperature carbonization treatment; wherein the low-temperature pre-oxidation treatment comprises: in an air atmosphere, heating the temperature to 100°C at a heating rate of 2°C / min and maintaining the temperature for 8 hours; the high-temperature carbonization treatment comprises: in a nitrogen atmosphere, heating the temperature to 1400°C at a heating rate of 2°C / min and maintaining the temperature for 2 hours, to obtain a modified hard carbon material, that is, an N-doped resin-derived carbon material.
[0171] The main difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses another modifier (N source) melamine for doping, which results in Comparative Example 3 being unable to graphitize and expand the interlayer spacing.
[0172] Comparative Example 4
[0173] The preparation of the modified hard carbon material comprises the following steps:
[0174] (a) Slowly add 50 mg of viscous modifier PDDA to 50 mL of 5 mg / mL carbon source solution (PF ethanol solution) and disperse evenly, keep the mixture in a water bath at 80° C. and stir for 5 h to obtain a pectin-like mixture.
[0175] (b) The pectin-like mixture obtained in step (a) was added with 100 mL of deionized water, transferred into a polytetrafluoroethylene reactor, reacted at 120° C. for 8 h, and freeze-dried to obtain a PDDA@PF precursor having a loose fungus shape.
[0176] (c) The precursor prepared in step (b) is heated to 1200° C. at a heating rate of 2° C. / min and kept at this temperature for 2 h to obtain a modified hard carbon material.
[0177] The main difference between Comparative Example 4 and Example 1 is that Comparative Example 4 is not subjected to pre-oxidation treatment, resulting in insufficient crosslinking, a low content of oxygen-containing functional groups, and reduced interlayer spacing.
[0178] Performance Testing
[0179] 1. Preparation of sodium ion batteries
[0180] (1) The modified hard carbon materials prepared in the above-mentioned embodiments and comparative examples were used as negative electrode active materials, conductive carbon black (Super P) was used as a conductive agent, and styrene-butadiene rubber (SBR) was used as a binder.
[0181] The negative electrode active material, the binder and the conductive agent are mixed in a mass ratio of 8:1:1 to obtain a mixed material, and the mixed material is fully stirred in deionized water to obtain a corresponding negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and after drying, pressing and other processes, a negative electrode sheet is obtained.
[0182] (2) Provide a metallic sodium sheet as the positive electrode sheet.
[0183] (3) A glass fiber membrane is provided as an isolation membrane.
[0184] (4) Providing an electrolyte solution, which is 1.0 mol / L NaPF 6 The product is prepared by dissolving in an organic solvent consisting of ethylene carbonate (EC) + dimethyl carbonate (DMC) + fluoroethylene carbonate (FEC) (the volume ratio of EC, DMC and FEC is 4.5:4.5:1).
[0185] (5) Assemble the negative electrode sheet, the isolation membrane, and the positive electrode sheet in order and soak them in electrolyte respectively to assemble into a CR2032 button battery in an argon glove box.
[0186] 2. Test the electrochemical performance of the battery
[0187] The GCD test was performed using a LAND battery test system in a voltage window of 0-2V.
[0188] (1) First discharge capacity and first charge capacity test: At a constant temperature of 25°C, discharge at a rate of 0.05C to 0.01V, and discharge at a constant current of 20uA to 0V, and record the rate discharge capacity + constant current discharge capacity = first discharge capacity at this time; continue to charge at a rate of 0.1C from 0V to 2V, and record the charge capacity at this time as the first charge capacity.
[0189] (2) First coulombic efficiency test: First coulombic efficiency = first charge capacity / first discharge capacity*100%.
[0190] (3) Capacity retention rate (cycle performance) test: Under the constant temperature condition of 25°C, discharge at a rate of 0.1C to 0V, and then charge at a rate of 0.1C to 2V. This is a complete charge and discharge cycle, which is recorded as 1 cycle. Repeat this process until the number of cycles is equal to 500, and then the test is terminated. The discharge capacity of the last cycle is the reversible specific capacity, and the discharge specific capacity of the last cycle / the discharge specific capacity of the first cycle = the capacity retention rate of 500 cycles.
[0191] (4) Rate performance test: At a constant temperature of 25°C, discharge at a rate of 0.1C to 0V, then charge at a rate of 0.1C to 2V, and cycle for 5 cycles to obtain a stable capacity. Then discharge at a high rate of 1C to 0V, then charge at a rate of 1C to 2V, and cycle for 5 cycles. Finally, the capacity discharged at a rate of 1C / the capacity discharged at a rate of 0.1C = the capacity retention rate at a rate of 1C (rate performance).
[0192] The test results are shown in Table 1 below.
[0193] Table 1
[0194]
[0195]
[0196] As can be seen from Table 1, compared with Comparative Examples 1-4, the button-type half-cells prepared using the modified hard carbon materials provided in Examples 1-8 have higher initial discharge capacity, higher first inventory efficiency, and good cycle performance and rate performance. This shows that the modified hard carbon material (carbon material derived from organic catalytic graphitized resin) prepared in the embodiment of the present invention, by affecting the process of further transformation of the structure of the carbon fiber to a turbostratic graphite structure or a graphite structure, effectively limits the formation and growth of graphitized domains and avoids the generation of defects during the melting process. Therefore, the carbonization product has a high degree of lattice disorder and a large interlayer spacing. At the same time, the amino group in PDDA as a nitrogen doping can improve the conductivity of the hard carbon, thereby obtaining excellent rate performance, and showing excellent cycle stability and rate performance.
[0197] also, Figure 2 The XRD patterns of the modified hard carbon material (PDDA@PF) and the common resin-based hard carbon material (PF) prepared in Example 1 of the present invention are shown. The interlayer spacing of the (002) crystal plane can be calculated based on the Bragg formula 2dsinθ=nλ from the XRD patterns of the hard carbons of different resin precursors. Figure 2It can be seen that compared with the ordinary resin-based hard carbon material (PF) of Comparative Example 1, the 2θ angle of the hard carbon material of the PDDA-PF sample prepared in the embodiment of the present invention shifts to the left, indicating that the interlayer spacing becomes larger, that is, the interlayer spacing can be effectively expanded by PDDA modification.
[0198] Figure 3 The Raman spectra of the modified hard carbon material (PDDA@PF) prepared in Example 1 of the present invention and the common resin-based hard carbon material (PF) are shown. Figure 3 It can be seen that the intensity ratio of the Raman D peak and the G peak can qualitatively characterize the disorder of the structure. According to calculations, the ID / IG of the PDDA-PF hard carbon sample is larger (the ratio increases from 1.02 to 1.65), indicating that the modified hard carbon material (PDDA@PF) provided in Example 1 of the present invention has a higher degree of disorder and an increase in the transmission channels of sodium ions, which is beneficial to the improvement of the kinetic properties.
[0199] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0200] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0201] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0202] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0203] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A modified hard carbon material, characterized in that: The modified hard carbon material comprises a carbon matrix and a doping element, wherein the doping element is distributed between carbon layers of the carbon matrix, and the doping element comprises N element; The modified hard carbon material is obtained by heat-treating a carbon source modified by a modifier, wherein the modifier comprises polydiallyldimethylammonium chloride.
2. The modified hard carbon material according to claim 1, characterized in that The carbon interlayer spacing of the carbon matrix is 0.3nm to 0.5nm; and / or, the mass of the N element accounts for 1% to 5% of the total mass of the modified hard carbon material; and / or, the modified hard carbon material has a fungus-like morphology; And / or, the carbon source includes an organic synthetic resin and / or a biomass resin, the organic synthetic resin includes at least one of a phenolic resin, an epoxy resin, a urea-formaldehyde resin, a melamine-formaldehyde resin, a polyester resin, a polyamide resin, an acrylic resin, a vinyl resin, a hydrocarbon resin or a polyether resin, and the biomass resin includes at least one of a starch phenolic resin, a lignin phenolic resin or a cellulose phenolic resin.
3. A method for preparing a modified hard carbon material as claimed in claim 1 or 2, characterized in that: The following steps are involved: Mixing the carbon source solution and the modifier to obtain a mixture; The mixture is mixed with a solvent, reacted at a first temperature for a first time, and dried to obtain a precursor; heat-treating the precursor to obtain the modified hard carbon material; Wherein, the modifier includes polydiallyldimethylammonium chloride.
4. The method for preparing a modified hard carbon material according to claim 3, characterized in that: The carbon source solution comprises a carbon source and an organic solvent; The carbon source comprises an organic synthetic resin and / or a biomass resin, wherein the organic synthetic resin comprises at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, melamine-formaldehyde resin, polyester resin, polyamide resin, acrylic resin, vinyl resin, hydrocarbon resin or polyether resin, and the biomass resin comprises at least one of starch phenolic resin, lignin phenolic resin or cellulose phenolic resin; And / or, the organic solvent includes an alcohol solvent.
5. The method for preparing a modified hard carbon material according to claim 4, characterized in that: The concentration of the carbon source solution is 1 to 10 mg / mL; and / or, the mass ratio of the modifier to the carbon source is 1:(5-10); And / or, the carbon source solution and the modifier are mixed at a mixing temperature of 40° C. to 100° C. and a mixing time of 2 h to 10 h.
6. The method for preparing a modified hard carbon material according to claim 3, characterized in that: The solvent includes water, the carbon source solution includes a carbon source and an organic solvent, and the volume of the water is 1 to 5 times the volume of the organic solvent; And / or, the first temperature is 100° C. to 200° C., and the first time is 5 h to 10 h; And / or, the drying method is freeze drying.
7. The method for preparing a modified hard carbon material according to any one of claims 3 to 6, characterized in that: The heat treatment includes a pre-oxidation treatment and a carbonization treatment performed sequentially; The pre-oxidation treatment is a heat treatment at a second temperature for a second time; The carbonization treatment is a heat treatment at a third temperature for a third time.
8. The method for preparing a modified hard carbon material according to claim 7, characterized in that: The second temperature is 50°C to 150°C, and the second time is 5h to 20h; And / or, the third temperature is 1000° C. to 1400° C., and the third time is 2 h to 5 h; And / or, the atmosphere during the pre-oxidation treatment includes air and / or oxygen; And / or, the atmosphere during the carbonization treatment includes at least one of nitrogen, argon, helium or neon; And / or, the heating rate of the pre-oxidation treatment is 0.5-5°C / min; And / or, the heating rate of the carbonization treatment is 0.5-5°C / min.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the modified hard carbon material according to any one of claims 1 to 2 or the modified hard carbon material obtained by the method according to any one of claims 3 to 8.
10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.
Citation Information
Cited By
Carbon material as well as preparation method and application thereof
CN119706795A
